(untitled) - Strutt, Peter (Harlow, England, 2013)
English for International Tourism is a three-level series designed to meet the English-language needs of professionals working in the tourism industry and students of tourism in further education. Using photos and maps from the world’s best-loved guidebooks, Dorling Kindersley’s Eyewitness Travel Guides, this is a highly-motivating way for learners to: develop language awareness, acquire specialized terminology, build confidence in professional skills needed in the tourism industry, practise language skills in realistic Case Studies. The DVD-ROM accompanying the Coursebook includes travel DVDs with accompanying worksheets.
Keywords: Tourism,English language,English languages,Tiếng Anh,Tiếng Anh,Du lịch; Terminology,Problems, exercises, etc.,Textbooks for foreign speakers,Sách giáo khoa cho người nước ngoài,Câu hỏi và bài tập,Thuật ngữ